Situation of Polish Graduate on the Labour Market - Wojtas, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Since 2008, the number of young people without work has increased to 166,000. Today, every fourth unemployed person is 25 years old, has graduated from college, and knows at least one foreign language. The main objectives of the article are to characterise this group, determine the type of unemployment that affects them, find the causes of that unemployment and to propose solutions primarily to improve the current situation of graduates on the labour market. Currently one in ten unemployed Poles has a higher education, though unemployment is still highest among those with a vocational education, secondary and primary or incomplete primary education. It is not only Poland but countries throughout Europe that face this problem. However, Poland has only just begun to realise the importance of its existence. What is to be done to combat unemployment? How can we help young people find their dream jobs? There are a number of ways to fight unemployment. The article proposes several key solutions that will enable young people to believe calling them the "Lost Generation" was a premature act.